Mortality of Exotic Pines in Plantation in India - Singh, Sujan; Khan, S. N. (Indian Forester, 1982)
Mortality of exotic pines in plantations Was recorded due to root-rot caused by Armilluriella mellea in North Bengal and due to development of deformed root system in Uttar Pradesh and Jdgdalpur (Madhya Pradesh). A. mellea exists in endemic stage in natural forests and developed a high inoculum potential on residual stumps after clearfelling natural forests. Infection of pines took place when pine roots came in contact with infected roots of decaying stumps. The fungus fromed abundant fruit bodies on decaying stumps and on dead pine plants. Absence of pine to pine spread of disease in the plantations indicates that the disease does not pose any ’serious problem at this stage. Armillariella root-rot in exotic pines is recorded for the first time in India. Development of deformed roof system may occur when the bag is left intact at the time of planting or when proper care is not taken at the time of pricking the seedlings in polythene bags or planting in the field. Recommendations are,given to encourage healthy root development in exotic pines by taking adequuate precautions at different stages of planting operations.